2016
DOI: 10.14687/ijhs.v13i1.3653
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Autonomy Support Scale for Exercise Settings: Validity and reliability study for Turkish<p>Egzersizde Algılanan Özerklik Desteği Ölçeği: Türkçe geçerlik ve güvenirlik çalışması

Abstract: The purpose of this study was to examine the validity and reliability of Perceived Autonomy Support Scale for Exercise Settings (PASSES; Hagger et al., 2007) from teacher and from peers in Turkish context. It was conducted with volunteer university students. 230 university students completed PASSES from teacher, and 142 university students completed PASSES from peers. Each scale has 12 items with a unidimension structure. The items were rated on a 7-point Likert type scale from totally disagree (1) to totally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The Cronbach's alpha value of the questionnaire was found to be .96. Muftuler (2016) revealed that the confirmatory factor analysis provided the good fit indices (χ 2 /sd = 2.33, p≤ .05, RMSEA =.076, CFI =.978; NFI =.963, SRMR =.035; GFI =.932). A sample item for this scale was that 'I feel that my PE teacher provides me with choices, options, and opportunities about whether to do active sports and/or vigorous exercise in my free time.…”
Section: Perceived Autonomy Support Scale For Exercise Settingsmentioning
confidence: 95%
See 2 more Smart Citations
“…The Cronbach's alpha value of the questionnaire was found to be .96. Muftuler (2016) revealed that the confirmatory factor analysis provided the good fit indices (χ 2 /sd = 2.33, p≤ .05, RMSEA =.076, CFI =.978; NFI =.963, SRMR =.035; GFI =.932). A sample item for this scale was that 'I feel that my PE teacher provides me with choices, options, and opportunities about whether to do active sports and/or vigorous exercise in my free time.…”
Section: Perceived Autonomy Support Scale For Exercise Settingsmentioning
confidence: 95%
“…The Perceived Autonomy Support Scale for Exercise Settings was used in the PE lesson to determine the students' perceptions of the autonomy support provided by the teacher in PE. It was developed by Hagger, Chatzisarantis, Hein, Pihu, Soos, and Karsai (2007), and the validity and reliability of the Turkish version were tested by Muftuler (2016). The scale comprises 12 items and is scored on a 7-point Likert scale, with responses ranging from "completely agree" to "completely disagree".…”
Section: Perceived Autonomy Support Scale For Exercise Settingsmentioning
confidence: 99%
See 1 more Smart Citation